Compromises in occupational choice and premature termination of vocational education and training: gender type, prestige, and occupational interests in focus - Fischer-Browne, Melanie; Ahrens, Lea; Kleinert, Corinna; Schels, Brigitte (Empirical Research in Vocational Education and Training, 2024)
This study examines whether premature termination of vocational education and training (VET) is more likely when trainees have to make compromises between their realistic occupational aspirations and the occupation for which they are trained in terms of the occupational dimensions of gender type, prestige, and occupational interests. Specifically, it examines the relative importance of the three compromise dimensions on premature VET termination. The study is based on a sample of 3,241 VET entrants from a cohort of ninth graders in 2010 in the German National Educational Panel Study (NEPS-SC4) in combination with aggregated data on occupational characteristics. Results from discrete hazard rate models indicate a higher risk of premature VET termination for trainees whose VET occupation differs from their realistic occupational aspiration from their school days. While compromises in prestige have no overall effect, both compromises in interests and gender type threaten the stability of VET. The results also indicate that compromises in interests have the strongest effect on the risk of premature VET termination and that the effects of compromises in gender type are partly mediated by the effects of compromises in interests. Furthermore, sensitivity analysis revealed that the main effects of compromises in gender type and prestige are gender specific.
CRIS-Team Scopus Importer:2024-08-09
Keywords: Gender type; Germany; Occupational compromising; Occupational interests; Premature termination of vocational training; Prestige